Mutation breeding for heat and drought tolerance in tepary bean (Phaseolus acutifolius A. Gray) - Muñoz, Ligia Carmenza; Debouck, Daniel G.; Rivera, Mariela; Muñoz, Jaime E.; Alpala, Deisy; Sarsu, Fatma; Rao, Idupulapati M. (Southern Cross Publishing, 2021)
Tepary bean (Phaseolus acutifolius A. Gray) is more heat and drought tolerant than common bean (P. vulgaris L.). Four hundred mutant lines of two tepary accessions (G40068 and G40159) were generated by ethyl methane sulfonate (EMS) treatment. In preliminary studies of the M5 mutant lines under abiotic stress, three mutant lines (CMT 38, CMT 109, CMT 187) were selected from six mutated lines based on morpho-physiological traits and superior yield and advanced to the M6 generation. The M6 mutant lines were uniform and genetically stable. These mutant lines and their original (M0) parents were evaluated for heat and drought tolerance under greenhouse conditions. Their performance was evaluated for morpho-physiological attributes, seed yield and yield components. Under high temperature and drought conditions, the CMT 38 mutant (M6 line) and its original tepary (M0) accession (G40068) showed greater values of pod biomass, pod number and 100-seed biomass than the other lines tested. The CMT 109 and CMT 187 mutant lines and their G40159 original accession (M0) also showed the highest value of seed number under high temperature and drought conditions. This suggests that the previous screening performed during the population advancement of these mutant lines, based on morphological traits like growth habit, was not detrimental to the yield variables evaluated here. Under combined heat and drought conditions, different parameters could be incorporated into tepary breeding programmes, as selection criteria to screen genotypes for tolerance to heat and drought stress. These parameters included: chlorophyll (SPAD) readings, seed biomass, 100-seed biomass and seed number because they explain the observed variance in the principal component analysis. Two additional traits (root biomass and stem diameter) were also identified as useful attributes, based on univariate analysis. The mutant lines evaluated here offer potential for further improvement of tepary bean to high temperature and drought.